On Design and Verification of an Efficient Microwave Wireless Power Transmission System - Baoxian Zheng; Kunding Ma; Yuanyuan Liu; Tong Jiang; Tingyi Liu; Qishuai Ma; Yi Liu; Lin Yang; Xi Li (International Journal of Antennas and Propagation)
We report on the theoretical design and experimental verification of a high efficiency microwave wireless power transmission (MWPT) system operating in the Fresnel region. To achieve high conversion efficiency over a transmit distance of 11 meters, the transmit reflector antenna was optimized to locate the focal point at 11 m. The size of the receive antenna was decided by calculating the field distribution and the received power at different positions in the receive antenna aperture. Furthermore, an accurate model of the diode is presented, which was imported into the ADS software for high-precision rectifying circuit design. As a result, an overall DC-DC conversion efficiency of 20% was achieved, as measured in an anechoic chamber at a given distance of 11 m. The experimental results validated the proposed method.